Evaluation of bentonite clay in modified and unmodified forms to remove fluoride from water - Adane Woldemedhin Kalsido (IWA Publishing, 2021)
The feasibility of fluoride adsorption from aqueous solutions using naturally available bentonite clay in both modified and unmodified forms is investigated in this report. Scanning electron microscopy (SEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy analysis was applied to describe the structure and nature of modified and unmodified bentonite clay. The physicochemical characteristics of the adsorbent were also investigated for moisture content, pH, apparent density, specific surface area, cation exchange capacity and its point-of-zero charge. SEM images reveal particles are dispersed homogeneously and are irregular in shape. XRD and EDX analyses reveal that the bentonite is composed of seven materials: calcite, silica, alumina, hematite, bornite and green cinnabar, and chloride which are considered as impurities. Raw bentonite clays have shown very low fluoride removal efficiency (47.19%). Modification of the clay surface with HCl and aluminum oxide, on the other hand, increased fluoride removal efficiency to 79.77% and 94.38%, respectively. At 5 mg/L initial fluoride concentration, 10 cm bed depth packed dose of adsorbent, and 180 min breakthrough time, a 2.88 mg/g of fluoride removal capacity was observed. As a result, aluminum oxide modified bentonite clay was chosen for further investigation and the results are not presented here. HIGHLIGHTS Clay minerals adsorption experimentation for low fluoride concentrations (5, 10, and 12 mg/L) was successful.; Most of the experimentation done so far are in batches using clay-based minerals and leads to shorter reaction times and thus are not at equilibrium.; Column experimentation using clay minerals was difficult, but this study used the clay as a filter media through surface modification of the adsorbent.;